Iluminación exterior, principios, diseño y aplicaciones - García Romero, Carlos; Quezada R., Juan José (My University, 1992)
INTRODUCTION. This information in previous chapters has detailed the general information required for a general working knowledge of what can be applied to Roadways Walkways and Bikeways. The basic examples and computation that follow apply to Roadways. It is obvius, however that the data and techniques can be applied to adjancent walkways, median strips and some other areas. For special computations relating to Area Lighting and high Mast Linghting refer to Appendices C & D of the 1977 American National Standard Practice for Roadway Lighting. In the Standard Practice definite facts are set up to outline what must be done to provide an installation of luminaires which will produce acceptable results.
Keywords: luz; superpostes; alumbrado; registro; mantenimiento